Algorithm of selecting the tear replacement therapy in ambulatory practice - V.V. Brzheskiy (РМЖ "Клиническая офтальмология")
Brzheskiy V.V. St. Petersburg State Pediatric Medical University Aim: to determine the algorithm for selecting artificial tears for tear-replacement therapy for patients with different etiopathogenesis and clinical course of the dry eye syndrome. Patients and Methods: the analysis of fragments of studies performed by us in different years, which is based on the results of examination, treatment and follow-up of 820 patients with dry eye syndrome of different etiology and with different clinical course of the disease with a comparative analysis of the efficacy of “artificial tear” preparations registered in Russia. Results: the choice of the «artificial tear» preparation depends on the pathogenesis of the dry eye syndrome, the severity of its clinical course and the concomitant pathology of the cornea and conjunctiva in a particular patient. The pathogenetic orientation of tear replacement therapy is based on the elimination of the cause of disorder in the tear film stability. “Artificial tear” preparations based on hyaluronic acid and other natural polysaccharides, as well as carboxymethylcellulose, are effective in case of mucin component deficiency. The aqueous layer can be replaced with any low viscosity, medium viscosity and high viscosity «artificial tear», and lipid layer - with Cationorm or Systein Balance preparations. The severity of the xerotic process determines the patient compliance to preparations with certain viscosity: preservative-free low-viscosity preparations are effective in case of mild and extremely severe xerosis, preservative-free high viscosity preparations and gels are most effective in moderate and severe xerosis, respectively. «Artificial tear» preparations containing additional ingredients (metabolic, anti-inflammatory, antioxidant, osmoprotective, etc.) are used depending on the concomitant pathology of the cornea and conjunctiva. Conclusion: further studies with the analysis of the effectiveness of new drugs will make it possible, on the one hand, to refine the algorithm we considered, and to develop pathogenetically oriented compositions of artificial tears, on the other. Key words: dry eye syndrome, tear-replacement therapy, artificial tears. For citation: Brzheskiy V.V. Algorithm of selecting the tear replacement therapy in ambulatory practice // RMJ “Clinical ophthalmology”. 2018;1:13–19.